2017
DOI: 10.1364/oe.25.018603
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the second plateau in solid high-order harmonic spectra by the two-color fields

Abstract: We theoretically investigate high-order harmonic generation (HHG) from solids in two-color fields. It is found that under the premise of maintaining the same amplitude, the intensity of the second plateau can be enhanced by two to three orders in a proper two-color field compared with the result in the monochromatic field with the same frequency as the driving pulse of the two-color field. This can be attributed to the fact that most excited electrons can be driven to the top of the first conduction band due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…More precisely, when the peak intensity of the laser changes by only 40%, the yield of the high order harmonic can be increased by 10–100 times in the energy range of E > 10 eV. Meanwhile, by simply controlling the amplitude ratio of the second beam to the first one, the cutoff of the plateau region can be further extended, showing the possibility to generate isolated attosecond pulses . The phenomena can be attributed to the fact that larger vector potentials are obtained when increasing r 2 coherently.…”
Section: Some Examples Toward Simulating Realistic Systemsmentioning
confidence: 99%
“…More precisely, when the peak intensity of the laser changes by only 40%, the yield of the high order harmonic can be increased by 10–100 times in the energy range of E > 10 eV. Meanwhile, by simply controlling the amplitude ratio of the second beam to the first one, the cutoff of the plateau region can be further extended, showing the possibility to generate isolated attosecond pulses . The phenomena can be attributed to the fact that larger vector potentials are obtained when increasing r 2 coherently.…”
Section: Some Examples Toward Simulating Realistic Systemsmentioning
confidence: 99%
“…For populations of C2, they move toward the top of the energy band when the vector potential is decreasing, for the negative correlation between E k 3 and k within the first BZ. When the vector potential is equal to zero, most populations can reach the top of C2 and then transit to C3 regardless of the laser field [29,30]. Population transition between bands 4 and 5 just can happen after the inversion of the driving electric field, which contributes the short trajectory predominantly, as can be seen from figure 3(c).…”
Section: Simulation Results and Discussionmentioning
confidence: 90%
“…Each electron is tunnel ionized to an upper band predominantly at the minimum band gap, e.g., from band 2 to 3 at k=0.0. And population transfer between bands 3 to 4 is mainly at the vicinity of the BZ edge [29][30][31]. For populations of C2, they move toward the top of the energy band when the vector potential is decreasing, for the negative correlation between E k 3 and k within the first BZ.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The HHG with different compositions of the driving laser pulses was addressed also for solid targets and nanostructures considering two distinct regimes. First, if the driving field consists of the fundamental wave and its harmonics [4,24,[49][50][51][52][53][54][55], and second, if one of the involved wave frequencies significantly higher than the other one [2,[56][57][58][59][60][61][62]. Two-color high-order wave mixing research reported so far has mainly been performed for gapped systems.…”
Section: Introductionmentioning
confidence: 99%